Modeling of Ice-Water Phase Change in Horizontal Annulus Using Modified Enthalpy Method (Advances in Applied Mathematics and Mechanics, 2021)
Phase change in ice-water systems in the geometry of horizontalcylindrical annulus with constant inner wall temperature and adiabaticouter wall is modeled with an enthalpy-based mixture model. Solidificationand melting phenomena under different temperature conditions areanalyzed through a sequence of numerical calculations. In the case of freezingof water, the importance of convection and conduction as well as the influenceof cold pipe temperature on time for the complete solidification is examined.As for the case of melting of ice, the influence of the inner pipe walltemperature on the shape of the ice-water interface, the flow and temperaturefields in the liquid, the heat transfer coefficients and the rate of meltingare analyzed. The results of numerical calculations point to good qualitativeagreement with the available experimental and other numerical results.